Analisis Pengaruh Jumlah Produksi, Luas Lahan, dan Kurs Dolar Amerika Terhadap Volume Ekspor Kopi Indonesia Periode Tahun 2001-2011 - Galih, Ambar Puspa; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 2, Februari 2014 (pp. 48 - 76), 2014)
Coffee as one of the commodity from the agriculture sector and as one of the main source income of Indonesia is a global commodity that is highly economic valued. As its role as an export commodity, coffee makes Indonesia as one of the world's leading coffee producers and ranks world's third-largest coffee producer after Brazil and Vietnam. The purpose of this study are to determine the effect of total production, land area, and the U.S dollar exchange rate simultaneously and partially to the volume of Indonesia’s coffee export and to determine which independent variable has dominant influence on the volume of Indonesia's coffee export in 2001-2011. Regression analysis is the analysis technique used. Results of analysis show that total production, land area, and the U.S. dollar exchange rate have simultaneously significant effect to the volume of Indonesia's coffee exports 2001-2011. Yet partially, only variable total production significantly effect the volume of Indonesia's coffee exports 2001-2011, while land area and U.S. dollar exchange rate did not have any significant effect on the dependent variable. Lastly, the most dominant variable that influent the volume of Indonesia’s coffee export in 2001-2011 is total production.
Keywords: coffee , international trade , export , production , exchange rate